Implementasi Metode Role-Play Berbasis Kecerdasan Spiritual Kristen di Sekolah Inklusi TK Talenta Semarang - Ela, Ela; Triposa, Reni; Octavianus, Steaven (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2024)
This research was conducted in an inclusive school that focused on the Quiet Time class at TK Talenta Semarang. By cultivating Christian spiritual intelligence that is centered on the character of students, as well as laying the foundation of faith as early as possible, through teaching that is based on the Bible and centered on Christ, with a role-play learning method approach. The existence of special children (Children with Special Needs) who have special needs in certain aspects, the author wants to research learning methods, using the role-play method which is centered on developing the abilities of special children in inclusive schools, which involves interaction and communication in a learning process activities, through role-play method learning activities. From the learning process activities of the role-play method based on spiritual intelligence, it is known and found that in the role-play method there are three other correlations of intelligence, namely: linguistic intelligence, movement-kinesthetic intelligence, and musical intelligence whose existence cannot be separated. This research was carried out to develop several intelligence, from Howard Gardner’s theory, including spiritual intelligence, linguistic intelligence, movement-kinesthetic intelligence, and musical intelligence, in children with special needs. The research method used is a qualitative descriptive method, with data analysis techniques from Miles and Huberman such as data collection, data reduction, data presentation, and drawing results from data verification conclusions, in the form of interviews, observations, documentation, and portfolio. The expected result of this research is the development of a curriculum in inclusive schools by the needs of students, which develops the potential of students. AbstrakPenelitian ini dilakukan, di sekolah inklusi yang berfokus pada kelas Saat Teduh di TK Talenta Semarang. Dengan adanya penanaman kecerdasan spiritual Kristen yang berpusat pada karakter peserta didik, serta meletakan dasar iman sedini mungkin, melalui pengajaran yang bersumber pada Alkitab dan berpusat pada Kristus, dengan pendekatan metode pembelajaran role-play. Keberadaan anak istimewa (Anak Berkebutuhan Khusus) yang memiliki kebutuhan khusus pada aspek tertentu, maka penulis ingin melakukan sebuah penelitian mengenai metode pembelajaran, dengan menggunakan metode role-play yang berpusat pada pengembangan kemampuan anak istimewa di sekolah inklusi, yang melibatkan adanya interaksi, komunikasi dalam suatu kegiatan proses pembelajaran, melalui kegiatan belajar metode role-play. Dari kegiatan proses belajar metode role-play berbasis kecerdasan spiritual, diketahui dan ditemukan bahwa metode role-play terdapat adanya tiga korelasi kecerdasan lainnya yaitu: kecerdasan linguistik, kecerdasan gerak-kinestetik dan kecerdasan musik yang tidak dapat dipisahkan keberadaannya. Penelitian ini dilakukan dengan tujuan untuk mengembangkan beberapa kecerdasan dari teori Howard Gardner yang diantaranya yaitu: kecerdasan spiritual, kecerdasan linguistik, kecerdasan gerak-kinestetik, dan kecerdasan musik, pada anak ABK. Metode penelitian yang digunakan adalah metode deskriptif kualitatif, dengan teknik analisis data dari Miles dan Huberman seperti: pengumpulan data, reduksi data, penyajian data dan penarikan hasil dari kesimpulan/verifikasi data, yang berupa wawancara, observasi, dokumentasi dan portofolio. Hasil yang diharapkan dari penelitian ini, adanya pengembangan kurikulum di sekolah inklusi sesuai dengan kebutuhan peserta didik, yang mengembangkan potensi peserta didik.